Optimization of Agricultural Waste as an Alternative Media for the Production of Xylanase Enzymes by a Consortium of Thermophilic Bacteria - Febriana, Tiara; Irdawati (Jurnal Serambi Biologi, 2024)
The xylanase enzyme is an extracellular enzyme that is capable of hydrolyzing hemicellulose into xylooligosaccharides and xylose. One of the benefits of the xylanase enzyme is as a paper and pulp bleach. This enzyme is produced by thermophilic bacteria with the substrate contained in Beechwood Xylan. However, using Beechwood Xylan is expensive, so other alternatives are needed at more affordable prices. Agricultural waste is believed to be able to replace Beechwood Xylan because it contains xylan. The aim of this research is to find the best waste substrate to replace Beechwood Xylan as a medium for a consortium of thermophilic bacteria to produce xylanase enzymes. This research was conducted at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University in December 2023. The method used was descriptive, using 3 types of agricultural waste, namely straw, rice husks, and corn with samples of thermophilic bacteria SSA2, SSA3, and SSA4. Enzyme activity was measured using a spectrophotometer with a wavelength of 540nm. The data obtained is analyzed and displayed in tabular form. The results of this study show that straw has the highest average xylanse enzyme activity of 9,289 Units/mL, and husks have the lowest average enzyme activity of 6,161 Units/mL.